Relationship Between Old-Aged Preferences Regarding Various Types of Physical Activity and Chronic Disease Status: A Cross-Sectional Study in Shanghai, China - Huang, Xiaojing; Zhu, Wenqing; Gao, Xiang; Yu, Dehua; Jin, Hua; Huang, Jiaoling; Yu, Wenya; Lv, Yipeng; Zhou, Liang; Chen, Ning; Yang, Yan; Wang, Zhaoxin; et al. (Frontiers in Public Health, 2022)
Background A lack of physical activity (PA) is a threat to public health. However, for the elderly, most PA abilities are limited. By focusing on the types and intensity of PA that the elderly can bear, this study aimed to reveal whether preferences regarding types of PA (including housework, transportation, and recreational activities) and their intensity were associated with health status. The main forms of PA include shopping, cooking, cleaning, walking, cycling, various fitness activities and other activities with a certain intensity. Methods Surveillance data on chronic diseases and their risk factors were collected from one district of Shanghai in 2017-2018. A Kish table was used for sampling 500 older adults, including the diagnosed group (chronic diseases diagnosed by physicians, n = 119), the abnormal group (not diagnosed but abnormal indicators detected in this investigation, n = 287) and the healthy group (n = 94). Multiple regressions were used to test the relationship between the various types, durations and intensities of PA the elderly individuals participated in and their health status. Results All three groups included a large proportion of older adults who participated in housework- and transport-related PA. The diagnosed group had the largest proportion (63.06% for housework-related PA; 87.39% for transport-related PA) and median minutes (17.14 min of housework-related PA per day; 30.00 min of transport-related PA per day). The diagnosed group had more metabolic equivalents (METs) of moderate-intensity PA than the two other groups (H = 33.01, P < 0.01), and more people met the WHO recommendation (χ2 = 34.71, P < 0.01). Diagnosis was associated with performing housework- and transport-related PA and moderate-intensity PA and with meeting the WHO's recommendation. Higher education levels were a positive factor for elderly individuals to participate in PA. Conclusions Transportation and housework activities are good targets for increasing PA in older adults. Diagnosis is associated with older adults' more PA.